Colorimetric and sensory characteristics of fermented cured sausage with Brazilian ostrich meat addition - Carlos Pasqualin CAVALHEIRO (Ciência e Tecnologia de Alimentos, 2013)
The aim of this study was to determine the colorimetric and sensory characteristics of a fermented cured sausage containing ostrich meat (Struthio camelus) and pork meat. Four treatments were performed: one with no ostrich meat (TC) and the others containing 19.08 (T1), 38.34 (T2), and 57.60% (T3) of ostrich meat and pork meat. Colorimetric analyses were measuring L*, a*, b*, C*, and hº. Sensory analysis was conducted assessing color, aroma, flavor, and texture at the end of the sausages’ processing. The sausages containing ostrich meat were statistically different from the control in the instrumental colorimetric analysis. In the sensory analysis, no significant differences were observed between the treatments for aroma, flavor, and texture. However, significant differences were found in the color of the sausages due to the high myoglobin content present in the ostrich meat, which resulted in a very dark color in the treatment with the highest percentage of this type of meat.